On the thermomechanical behavior of model composites using digital image correlation - Zago, Igor Paganotto (2024)
In composite systems with incompatibility between the coefficients of thermal expansion (CTE) of their phases, stresses can lead to cracking of the material during a temperature variation. Analytical, numerical and experimental studies on the subject have been carried out. Experimentally, this topic is difficult to approach, since observing and measuring the effects of temperature variation in composite systems is not a trivial task. With the development and improvement of field measurement techniques such as Digital Image Correlation (DIC), a new approach is proposed in combination with the use of model composites. In the present study, mechanical and thermal properties of model composites phases composed of alumina and colloidal silica matrices with cylindrical inclusions of brass or zirconia were evaluated, and temperature variation experiments aided by DIC were carried out to obtain experimental displacement and strain fields. The model composites temperature variations were conducted up to 300, 600 or 900 ○C depending on the systems’s response up to that temperature. Such experiments allow the visualization of the model composites cracking, which can be quantified in terms of crack initiation and evolution. The quantification of cracking was done from the calculation of an inelastic strain field. Obtaining this field of both opposite faces of the tested systems and quantifying its cracking provides data for comparison with analytical and numerical modeling of cracking phenomena due to CTE incompatibility of such systems, results that do not exist in the literature. Thus, the data produced allows the modeling of this phenomenon to be carried out for the proposed composite systems, using the evaluated properties and having field information and parameterized cracking parameters for comparison.